Estimating the Effects of the Trans-Pacific Partnership (TPP) on Latin America and the Caribbean (LAC) - Cerdeiro, Diego (Washington, D.C. : International Monetary Fund, 2016)
In February 2016, twelve Pacific Rim countries signed the agreement on the Trans Pacific Partnership (TPP), one of the largest and most comprehensive trade deals in history. While there are several estimates of the likely effects of the TPP, there is no systematic study on the effects on all Latin American countries. We present the results from applying a multi-sector model with perfect competition presented by Costinot and Rodriguez-Clare (2014). The exercise, based on input-output data for 189 countries and 26 sectors, shows that (i) Asian TPP members are estimated to benefit most from the agreement, (ii) negative spillovers to non-TPP LAC countries appear to be of a different order of magnitude than the gains of members, and (iii) some non-TPP LAC countries may experience relatively large benefits from joining the TPP. As a cautionary note, however, we point out that even a cursory cross-study comparison shows that there is considerable uncertainty regarding the potential effects of the TPP for both members and non-members.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet